Conservative Music Criticism, the Inflation, and Concert Life in Weimar Germany, 1919–1924. Issue 2 (October 2017) - Fay, Brendan
Abstract : In surveying the thirteen crisis-ridden years that Weimar democracy endured from its founding in 1919, perhaps none loom as large as the hyperinflation years spanning 1922–1923. According to many historians, the 'Great Disorder' not only destroyed the bonds between different social classes but also shattered Germans' faith in and commitment to Weimar democracy. At the same time, Germany's cultural conservatives found themselves weathering a 'cultural crisis' brought on by the combined forces of artistic and technological innovation. In this article, I argue that our sense of Weimar's crises has been profoundly shaped by knowledge of what came later, and has tended to differ markedly from contemporaries' sense of history and their place in it. This article examines the inflation's impact on German concert life, reassessing cultural conservatives—long held as hostile to Weimar democracy—and their attitudes toward German classical music, the nation, and society during the turbulent early years of the Weimar Republic.